The Fraction of Intercepted Radiation to Nitrogen Absorption as an Indicator for Assessing Physiological Nitrogen Use Efficiency in Rice - Min Huang; Jiana Chen; Fangbo Cao (Agronomy, 2022)
Improving nitrogen (N) use efficiency is important for achieving sustainable rice production in China. Physiological N use efficiency (PNUE) is a measure of a plant’s ability to convert absorbed N into biomass, and can be calculated as the product of the fraction of intercepted radiation to N absorption (FIRNA) and radiation use efficiency (RUE). This study evaluated the relationships between PNUE with FIRNA and RUE in three widely grown, high-yielding rice varieties using data obtained from two N fertilization experiments conducted in 2020 and 2021. The results show that PNUE was significantly positively related to FIRNA, but not significantly related to RUE in all three rice varieties. PNUE increased by 7.4–10.3 g g−1 for each 10 MJ g−1 increase in FIRNA. These results suggest that FIRNA can serve as an indicator for assessing PNUE in rice, which has implications for the phenotypic identification of rice varieties with high PNUE.